Implementation of Critical Path Method (CPM) in Project Management of Type 45 House Construction in Samarinda - Ningsih, Armini; Surahman, Surahman; Ariani Aisyiah, Septi; Syahara, Adelia; Bayhaqi, Achmad (Journal of Business Management and Economic Development, 2025)
Project management is a very important area to ensure that projects are successful, especially in terms of achieving their goals on time, within budget, and to the set quality.  With a focus on planning, organizing, executing, and controlling projects, this study aims to examine how project management principles are applied in the implementation of construction projects in Indonesia. The method used was descriptive qualitative, and data were collected through literature research and documentation. The results showed that the understanding and application of project management methods such as Critical Path Method and cost and time control approaches have a great impact on project efficiency and efficiency.  Therefore, it is highly recommended to improve management skills as well as the use of information technology in project management to improve overall project performance.